SOCIAL MEDIA MARKETING AND BRAND EQUITY: THE INTERPLAY OF BRAND TRUST AS DRIVERS COSTUMER LOYALTY (Studi Kasus Pada Pelanggan Sabun Lux di Kota Semarang Dan Sekitarnya) - wea, yuliana (ITB AAS Indonesia Surakarta, 2024)
This study aims to examine the influence of Brand Equity, Social Media Marketing, and Brand Trust on Customer Loyalty to Lux Soap products in Semarang City. Tight competition in the personal care industry, especially soap, requires companies to not only maintain product quality, but also build customer trust and loyalty through brand equity and effective marketing strategies. This study uses a quantitative approach with a questionnaire method distributed to 145 respondents who are Lux Soap users. AMOS software was utilized to facilitate the application of the Structural Equation Modeling (SEM) technique for data analysis. The results of the study indicate that Brand Equity and Social Media Marketing have a positive and significant effect on Brand Trust, which in turn increases Customer Loyalty. This study contributes to the development of more effective marketing strategies through a deeper understanding of the relationship between brand equity, social media marketing, and brand trust in increasing customer loyalty. The practical implication of this study is that companies need to strengthen their presence on social media and build strong brand equity to increase customer trust and loyalty.